Natural killer T cells: innate lymphocytes positioned as a bridge between acute and chronic inflammation? - Fox, Lisa (2010)
Natural killer T cells are an innate population of T lymphocytes that recognize antigens derived from host lipids and glycolipids. In this review, we focus on how these unique T cells are positioned to influence both acute and chronic inflammatory processes through their early recruitment to sites of inflammation, interactions with myeloid antigen presenting cells, and recognition of lipids associated with inflammation.